Peripheral ossifying fibroma - Ameet Mani; Shubhangi Mhaske; P P Marawar; Sanjay Lagdive; Jitendra V Kalburge (Wolters Kluwer Medknow Publications, 2010)
The peripheral ossifying fibroma (POF) is an exophytic gingival mass of fibrous connective tissue covered with a surface epithelium associated with the formation of randomly dispersed foci of a mineralized product consisting of bone, cementum-like tissue, or dystrophic calcifications having a recurrent rate of nearly 20%. It is one of the most common reactive gingival lesions, which have often been called by the generic term "epulis." This case report describes the clinical and histopathological findings of POF, its differential diagnosis, and treatment.